Eine neue Pseudopsis-Art aus Nepal und neue Funde von Pseudopsis-Arten (Coleoptera: Staphylinidae, Pseudopsinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2000)
Pseudopsis crenata sp. n. is described from the southern slope of the Annapurna range, Nepal, and compared with related and similar species. Its aedeagus and pronotum are figured. The key to the Palaearctic species by Zerche (1998) is modified to include the new species. Pseudopsis susae Herman, 1983 is recorded from China for the first time. A further record of Pseudopsis watanabei Herman, 1975 from Honshu is given. Nomenclatural Acts crenata Zerche, 2000 (Pseudopsis), spec. n.